(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the multifaceted role of iconicity in expressing sensory perception across various languages and cultural contexts. Iconicity, the property by which linguistic forms bear a resemblance to their meanings, has significant potential to communicate sensory experiences. Drawing on the works of international and Uzbek scholars, this study investigates how iconic forms – particularly onomatopoeic expressions, ideophones, and sound-symbolic words – enable speakers to express rich perceptual experiences, such as vision, hearing, taste, and tactile sensations. Methodologically, this research employs a comparative analysis of linguistic examples, ethnographic accounts, and experimental findings from published scientific studies. The results illustrate that iconicity operates as a cognitive bridge connecting linguistic structures to non-linguistic experiences of the world, highlighting that language is not just an abstract system of symbols but also a means of mimetically representing reality. These insights can inform further research in semiotics, cognitive linguistics, and cross-cultural communication.